Readiness for the Implementation of Building Information Modeling (BIM) in Controlling Construction Costs for Public Works Projects During a Crisis in Timor-Leste - Lay, Denilson Pereira; Alrasyid, Harun; Nurhidayah, Nurhidayah (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the readiness for implementing Building Information Modeling (BIM) in controlling construction costs for public works projects during a crisis in Timor-Leste. General Background: Public construction projects are complex and frequently face cost overruns and delays, particularly under crisis conditions such as economic instability and supply chain disruptions. Specific Background: BIM, particularly 5D BIM, offers integrated digital solutions for improving cost estimation, information transparency, and project coordination. Knowledge Gap: Limited research addresses BIM implementation readiness by considering structural, technical, and institutional dimensions simultaneously, especially in developing countries during crises. Aims: This study aims to analyze BIM implementation readiness, identify key challenges, and examine its role in construction cost control during crisis situations. Results: Findings indicate that BIM readiness remains at an early stage, characterized by low stakeholder understanding, limited human resources, inadequate infrastructure, and lack of policy support, while project practices are still dominated by fragmented and conventional systems. Novelty: The study introduces a systemic readiness perspective integrating structural, technical, and institutional factors within a crisis context. Implications: The results highlight the need for a comprehensive approach involving human resource development, digital infrastructure strengthening, and regulatory support to facilitate BIM adoption and improve cost control responsiveness in public construction projects. Highlights: Early-stage adoption is marked by limited expertise, infrastructure constraints, and minimal institutional backing. Project management practices remain fragmented with reliance on manual and non-integrated systems. Systemic alignment of structural, technical, and regulatory elements is required for digital transition. Keywords: Building Information Modeling (BIM), Cost Control, Public Construction Projects